2008
DOI: 10.1074/jbc.m703177200
|View full text |Cite
|
Sign up to set email alerts
|

TRPC4 in Rat Dorsal Root Ganglion Neurons Is Increased after Nerve Injury and Is Necessary for Neurite Outgrowth

Abstract: Canonical transient receptor potential (TRPC) receptors are Ca2؉ -permeable cation channels that have a variety of physiological functions and may be involved in neuronal development and plasticity. We investigated the expression profile of TRPC channels in adult rat dorsal root ganglia (DRG) after nerve injury and examined the role of TRPC4 in neurite outgrowth in cultured DRG neurons. Sciatic nerve transection and microinjection of dibutyryl cAMP were employed to induce axonal regeneration in vivo. TRPC4 mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 50 publications
3
66
0
1
Order By: Relevance
“…2B). We also isolated mRNA from lysates of dissociated DRG neurons and detected TRPC5 transcripts (24). TRPC5 also is present in human tissues, and immunolabeling demonstrated that TRPC5 is expressed in intraepithelial nerve endings within the human skin (Fig.…”
Section: Trpc5mentioning
confidence: 99%
“…2B). We also isolated mRNA from lysates of dissociated DRG neurons and detected TRPC5 transcripts (24). TRPC5 also is present in human tissues, and immunolabeling demonstrated that TRPC5 is expressed in intraepithelial nerve endings within the human skin (Fig.…”
Section: Trpc5mentioning
confidence: 99%
“…Given the exclusive expression pattern of all three Mrg receptors in DRG, we tested species-specific alterations of receptor endocytosis in a second DRG-like cell line. ND-C cells have been established as a model system to analyze the pharmacological properties of DRG-specific proteins on the cellular level (Wood et al, 1990;Tang et al, 1994;Wu et al, 2008); thus, we have chosen these cells to further determine species-specific differences in Mrg receptor endocytosis. Stimulation of ND-C cells transfected with the respective cDNAs coding for Ex-tagged Mrg receptors confirmed that both rodent MrgC receptors are prone to agonistpromoted endocytosis either induced by BAM8-22 or ␥ 2 -MSH and that hMrgX1s resist BAM8-22-promoted endocytosis (Fig.…”
Section: Calcium Signaling and Receptor Endocytosis In Hek293 Cells Smentioning
confidence: 99%
“…heart, brain, sperm TRPC3 1/1.5-1.6 DAG, InsP 3 R Brain, placenta, heart, muscle Hippocampal neurons↑ [14] TRPC4 1/7 Receptor-operated Brain, endothelia, adrenal gland, DRG neurons↑ [26] Store-operated? retina, testis Hippocampal neurons↓ [18] TRPC5 1/9-9.5 Receptor-operated Brain PC12 cells↓ [27] Store-operated?…”
Section: Discussionmentioning
confidence: 99%
“…TRPC4, which belongs to the same subfamily as TRPC5, inhibits dendritic growth in hippocampal neurons [18] . However, suppression of TRPC4 by a specifi c siRNA or shRNA signifi cantly reduces the length of neurites in cultured dorsal root ganglion neurons [26] . Meanwhile, opposing regulatory effects of TRPC1 and TRPC5 on neurite outgrowth in PC12 cells have been reported [27] .…”
Section: Developmentmentioning
confidence: 99%